The Multiple Effects of Precursors on the Properties of Polymeric Carbon Nitride - Wendong Zhang; Qin Zhang; Fan Dong; Zaiwang Zhao (International Journal of Photoenergy)
Polymeric graphitic carbon nitride (g-C3N4) materials were prepared by direct pyrolysis of thiourea, dicyandiamide, melamine, and urea under the same conditions, respectively. In order to investigate the effects of precursors on the intrinsic physicochemical properties of g-C3N4, a variety of characterization tools were employed to analyze the samples. The photocatalytic activity of the samples was evaluated by the removal of NO in gas phase under visible light irradiation. The results showed that the as-prepared CN-T (from thiourea), CN-D (from dicyandiamide), CN-M (from melamine), and CN-U (from urea) exhibited significantly different morphologies and microstructures. The band gaps of CN-T, CN-D, CN-M, and CN-U were 2.51, 2.58, 2.56, and 2.88 eV, respectively. Both thermal stability and yield are in the following order: CN-M > CN-D > CN-T > CN-U. The photoactivity of CN-U (31.9%) is higher than that of CN-T (29.6%), CN-D (22.2%), and CN-M (26.8%). Considering the cost, toxicity, and yield of the precursors and the properties of g-C3N4, the best precursor for preparation of g-C3N4 was melamine. The present work could provide new insights into the selection of suitable precursor for g-C3N4 synthesis and in-depth understanding of the microstructure-dependent photocatalytic activity of g-C3N4.